Effect of flue gas composition on deposit induced high temperature corrosion under laboratory conditions mimicking biomass firing. Part I: Exposures in oxidizing and chlorinating atmospheres. Issue 5 (5th December 2016) - Okoro, S. C.; Kiamehr, S.; Montgomery, M.; Frandsen, F. J.; Pantleon, K.
Abstract : In biomass fired power plants, deposition of alkali chlorides on superheaters, as well as the presence of corrosive flue gas species, give rise to fast corrosion of superheaters. In order to understand the corrosion mechanism under this complex condition, the influence of the flue gas composition on high temperature corrosion of an austenitic superheater material under laboratory conditions mimicking biomass firing is investigated in this work. Exposures involving deposit (KCl)‐coated and deposit‐free austenitic stainless steel (TP 347H FG) samples were conducted isothermally at 560 °C for 72 h, under both oxidizing and oxidizing‐chlorinating atmospheres, and the resulting corrosion products were comprehensively studied with scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDS), and X‐ray diffraction (XRD) techniques. The results show that deposit‐free samples suffer grain boundary attack only in an oxidizing‐chlorinating atmosphere, otherwise corrosion results in formation of a duplex oxide. Corrosion attack on deposit‐coated samples was higher than on deposit‐free samples irrespective of the gaseous atmosphere. Specifically, severe volatilization of alloying elements occurred on deposit‐coated samples under oxidizing‐chlorinating atmosphere due to enhanced impact of KCl and HCl. Abstract : The high temperature corrosion of the austenitic stainless steel, TP 347H FG under conditions mimicking biomass firing is enhanced both by the presence of a deposit (KCl) and HCl in the flue gas. While chlorination in the absence of a deposit induces grain boundary attack, enhanced chlorination in the presence of a deposit results in severe volatization of chlorides of the alloying elements.